Digital empowerment for innovative teaching: application and mediating effects of information technology in physical education teachers’ practices - Zhao, Bochuan; Chen, Junji; Yang, Jiefu; Su, Yuqi (Frontiers in Sports and Active Living, 2025)
IntroductionAs innovative teaching and technology integration become increasingly important in physical education (PE), challenges remain in equipping teachers with necessary skills and resources. This study explores the current situation and relationship between PE teachers’ use of information technology (IT) for innovative teaching.MethodsA sample of 217 PE teachers completed a questionnaire measuring demographic variables, IT teaching, and innovative teaching performance. Quantitative analyses, including descriptive statistics, t-tests, ANOVA, and multiple regression, were conducted using SPSS.ResultsResults showed significant differences in IT teaching based on gender (t = −2.15, p < .05) and equipment adequacy (F = 4.24, p < .01). Participation in research and advanced education led to higher innovative teaching, especially in evaluation and management (t = 3.14, p < .01). IT teaching positively predicted innovative teaching performance, with document software having the strongest impact (β = .28, p < .001) on assessment and management. Mediation analysis revealed that teaching methods and content fully mediated the relationship between IT teaching and assessment and management.DiscussionThe findings suggest that IT integration allows PE teachers to create more diverse and innovative learning experiences. However, challenges related to teachers’ IT skills and school technology infrastructure need to be addressed. Implications for teacher training, technology policies, and curriculum design are discussed. Future studies could adopt longitudinal designs and mixed methods to further investigate the dynamic processes and mechanisms underlying technology-enhanced innovation in PE.